Distinguishing Good from Evil Through Art - Chowdhury, Kapil (International Journal of Control and Automation, 2018)
In order to achieve his psychological goals of uncovering the roots of moral attitudes as well as a revaluation for values, Nietzsche employed a wide range of artistic methods, including rhetorical techniques, concern for language texture, evaluation of his writings in terms of state of mind and tempo, as well as incitement of the the reader affects. It is believed that his writing style is fundamental to his goals, given his idea that moral attitudes originate largely in inherited affects. Nietzsche's writing elicits conflicting feelings towards slaves and nobility because of its representation in Genealogy I. Section 14 of Genealogy I has a comedic depiction of a character called "Mr. Rash and Curious," who is present at the fictitious establishment of the Christian virtues "good" and "evil." One interpretation is that the reader's response to the nobility primes their distaste for aggressiveness, which is then channelled into revulsion at the repressed anger that underpins these principles.